Physicochemical and Rheological Characterization of a Novel Manna Exudate from Alhagi pseudalhagi (Iranian Tarangabin) - Shahriyar Salehi; Fatemeh Raouf Fard; Seyed Mohammad Hashem Hosseini; Hadi Hashemi; Mehrdad Niakousari (Journal of Food Quality)
Tarangabin manna (TM) is a resinous substance having a yellowish sticky character with a reasonably sweet taste. It is largely collected in Iran and Afghanistan. This study for the first time presents a comprehensive investigation of the techno-functional, rheological, and interfacial characteristics of water-soluble components for TM. The composition analysis revealed protein, moisture, fat, ash, and carbohydrate contents of 1.58, 2.98, 0.51, 2.04, and 92.90%, respectively. The effects of TM concentration on the physicochemical, structural, rheological, interfacial, emulsion, and foaming ability and stability were evaluated. X-ray diffraction analysis showed an amorphous structure for the purified sample and a crystalline structure for the raw sample. TM solutions exhibited Newtonian behavior, with the apparent viscosity decreasing as temperature increased, fitting well with the Arrhenius model. The TM solutions exhibited weak viscoelastic properties, primarily demonstrating a dominant viscous character. The surface tension and interfacial tension of the TM solution prepared at a concentration of 50% were measured at 45.23 mN/m and 7.74 mN/m, respectively. The contact angle of the dry thin layer of TM was determined to be 31.74°. Remarkably, the TM solution at a concentration of 50% exhibited the highest foaming ability (76.80%), foaming stability (91.92%), and emulsifying activity index (24.53%). The findings, coupled with TM appropriate foaming ability and stability, sweetness, and characteristic flavor, suggest that TM holds potential as a special food ingredient.